Expression of β-catenin in gastroenteropancreatic endocrine tumours: a study of 229 cases. Issue 12 (26th May 2006) - Hervieu, V; Lepinasse, F; Gouysse, G; Guillaud, O; Barel, C; Chambonniere, M-L; Bringuier, P-P; Poncet, G; Lombard-Bohas, C; Partensky, C; Chayvialle, J-A; Scoazec, J-Y
Abstract : Aims: To clarify the role of β-catenin in digestive endocrine carcinogenesis, a large and representative series of gastroenteropancreatic endocrine tumours was analysed in order to determine the incidence and pattern of β-catenin changes and to analyse the clinical and histological characteristics of the tumours presenting immunohistochemically detectable changes in β-catenin expression. Methods: 229 cases of gastroenteropancreatic endocrine tumours (stomach, 11; duodenum and ampulla, 29; jejunum and ileum, 51; appendix, 13; colon and rectum, 17; and pancreas, 108) were studied by immunohistochemistry to assess the pattern of distribution of β-catenin (membranous, cytoplasmic or nuclear). DNA was analysed to detect mutations in exon 3 of the CTNNB1 gene. Results: The distribution of immunoreactive β-catenin protein was membranous in 164 cases, cytoplasmic in 58 cases and nuclear in seven cases. No mutation was detected in exon 3 of the CTNNB1 gene in any case. The seven cases with nuclear accumulation of β-catenin were large tumours (mean size 44 (standard deviation (SD) 18.5) mm) with metastases, including liver metastases in five cases, high Ki-67 index (mean 34% (SD 16.5%)) and cyclin D1 overexpression; p53 accumulation was detected in six cases. Five patients died of disease; the mean (SD) survival was 13.6 (4.8) months. Conclusions: Immunohistochemically detectable nuclear accumulation of β-catenin is infrequent in gastroenteropancreatic endocrine tumours and is usually not associated with mutations in CNNTB1 exon 3. Changes in β-catenin expression are late events in digestive endocrine carcinogenesis, associated with tumour progression and dissemination.